Management of diabetes in resource-poor settings - Grant, Paul (Clin Med (Lond), 2013)
Diabetes mellitus is an emerging problem in the developing world. In sub-Saharan Africa, for example, the incidence and prevalence of the disease is unknown, diagnosis is often made on the basis of poor information and a loosely defined set of criteria, and access to oral hypoglycaemic agents and insulin is patchy and expensive. The best system of management is currently unclear and this article explores lessons learnt, good practice and the applicability of the structured ‘directly observed treatment, short course’ (DOTS) approach (the current best care system for tuberculosis disease management in resource-poor settings) to the management of chronic diseases such as diabetes.